THE IMPACT OF INSTAGRAM USE ON TEENAGERS' SOCIAL INTERACTION AND EDUCATION - Ariani Songli; Suyato; Jawatir Pardosi; Ranita Eka Desti Rahmawati; Maria Antoneta Karbeka (SOSIOEDUKASI, 2025)
In today's digital era, thel use ofl social lmedia, especially Instagram, has lbecome an important partl of teenagers' llives. However, despite its benefits, excessive usel of Instagram canl have al negative impactl on teenagers' social interactions and learning processes. Thel purpose of this study is to explore the impact of Instagram use on teenagers' social interactions and education and to understand the role of Instagram as an effective and balanced educational tool, as well as the negative impacts that can arise if Instagram use is not regulated wisely. This is a qualitative descriptive study. The research informants included three students. Data was collected through techniques such as interviews, observation, and documentation. Data analysis techniques included data collection, data reduction, data presentation, and data conclusion. The results of the study indicate that the use of Instagram by teenagers has both positive and negative impacts. On the one hand, Instagram strengthens social interactions with friends and teachers and increases self-confidence through the sharing of experiences and creative content. However, excessive use also causes disruption to learning focus, reduces time for academic tasks, and disturbs sleep quality. Uncontrolled use of Instagram can affect learning motivation and academic achievement.